2016
DOI: 10.1371/journal.pone.0161843
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Women’s Experiences before and after the Introduction of Mifepristone into Second-Trimester Medical Abortion Services in South Africa

Abstract: ObjectiveTo document clinical outcomes and women’s experiences following the introduction of mifepristone into South African public sector second-trimester medical abortion services, and compare with historic cohorts receiving misoprostol-only.MethodsRepeated cross-sectional observational studies documented service delivery and experiences of women undergoing second-trimester medical abortion in public sector hospitals in the Western Cape, South Africa. Women recruited to the study in 2008 (n = 84) and 2010 (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…10 Constant et al in their study of clinical outcome before and after introduction of mifepristone in second trimester abortion services in South Africa concluded that this regimen has been successful in reducing the induction abortion interval, decreasepain, and had greater acceptability by women, but there were higher rates of placental retention and need for surgical evacuation for the same in their study. 11 But we did not have any case of placental retention.…”
Section: Discussionmentioning
confidence: 78%
“…10 Constant et al in their study of clinical outcome before and after introduction of mifepristone in second trimester abortion services in South Africa concluded that this regimen has been successful in reducing the induction abortion interval, decreasepain, and had greater acceptability by women, but there were higher rates of placental retention and need for surgical evacuation for the same in their study. 11 But we did not have any case of placental retention.…”
Section: Discussionmentioning
confidence: 78%
“…Closely related to task sharing was, for first‐trimester abortions, the widespread use of low technology procedures requiring little infrastructure: MVA and medical abortion using combination mifepristone‐misoprostol. Midwives, nurses, and other cadres of providers newly included under the task‐sharing rubric, were readily able to learn and employ these techniques . However, in two of the higher HDI countries (Portugal and Uruguay), the Ministry of Health also decided to provide medical abortion almost exclusively.…”
Section: Innovationmentioning
confidence: 99%
“…Midwives, nurses, and other cadres of providers newly included under the task-sharing rubric, were readily able to learn and employ these techniques. 52,56,57,[60][61][62][63][64] However, in two of the higher HDI countries (Portugal and Uruguay), the Ministry of Health also decided to provide medical abortion almost exclusively. This decision was made for similar logistical reasons, as medical abortion requires less infrastructure and training, and for political reasons, as it was anticipated that there would be less provider resistance to medical rather than surgical abortion.…”
Section: Innovationmentioning
confidence: 99%
“…For second-trimester services, the economic evaluation presented health service costs and cost-effectiveness for D&E and medical induction with and without mifepristone [21]. The clinical data for the second-trimester economic evaluation were collected in hospitals in Western Cape Province as part of a clinical trial in 2012-2013 [24] and a separate cross-sectional study that included observations in 2008, 2010, and 2014 [4,25].…”
Section: Costs and Cost Effectivenessmentioning
confidence: 99%
“…In the second trimester, dilation and evacuation (D&E) is available in a limited number of high volume settings, most, if not all, in one province. Medical induction services performed with misoprostol only are the standard nationwide, although, in 2014, one province changed their medical induction regimen to include mifepristone [4].…”
Section: Introductionmentioning
confidence: 99%